2013
DOI: 10.1136/emermed-2013-202395
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of patients administered blood in the prehospital environment by a road based trauma response team

Abstract: There is a potential role for prehospital pRBC transfusions in an integrated civilian trauma system. The RTS calculated using the initial set of observations may be a useful tool in determining in which patients the administration of prehospital pRBC transfusions would be futile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 13 publications
0
28
0
4
Order By: Relevance
“…Haemothorax was also specifically excluded in six cases. Although Bodnar et al [27] primarily examined a cohort of patients who received a blood transfusion in a prehospital setting, they reported the diagnosis of haemoperitoneum as a secondary outcome which they found in 39% of their scanned patients. Mazur et al [29] reported a positive diagnosis of pneumothorax or free peritoneal fluid in 6 of 30 cases.…”
Section: Findings Of Individual Studiesmentioning
confidence: 94%
See 3 more Smart Citations
“…Haemothorax was also specifically excluded in six cases. Although Bodnar et al [27] primarily examined a cohort of patients who received a blood transfusion in a prehospital setting, they reported the diagnosis of haemoperitoneum as a secondary outcome which they found in 39% of their scanned patients. Mazur et al [29] reported a positive diagnosis of pneumothorax or free peritoneal fluid in 6 of 30 cases.…”
Section: Findings Of Individual Studiesmentioning
confidence: 94%
“…The studies all had limited enrolment, inconsistent patient follow-up, and no assessment of morbidity or mortality. Due to the observational nature of the study designs, the best grade that could be achieved on the SIGN level of evidence grading was a 2+ [23], with three studies achieving this level [9,26,27].…”
Section: Methodological Quality/risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some studies have begun to reveal the feasibility of blood administration in the field under select circumstances, one of them being helicopter emergency medical services (HEMS) operations -both primary responses and interfacility critical care transfers involving patients with major trauma. [1][2][3][4] One of the significant challenges of transporting and administering blood in a HEMS environment relates to preserving the required blood storage temperature during missions that may last several hours. Helicopters represent an austere environment for both patient care and storage of temperaturesensitive drugs and fluids with little space, severe limitations on access to external power sources and exposure to thermal variations caused by environmental, diurnal and seasonal changes.…”
mentioning
confidence: 99%